Geochemistry of Engineered Nanoparticles (CdSe/ZnS Quantum Dots) in Surface Waters - Supiandi, N. Izyan; Domingos, Rute F.; Benedetti, Marc F.; Sivry, Yann (Frontiers in Environmental Science, 2020)
The difficulties when studying the behavior of engineered nanoparticles (ENPs), and the subsequent metal speciation in aquatic ecosystems, at environmentally relevant concentrations (i.e., ppt level) are often related to the occurrence of ENP constitutive elements at high concentrations as a background in aquatic media. In this study, the physicochemical behavior of CdSe/ZnS quantum dots (QDs) when spread at very low concentrations in surface waters was investigated. The above-mentioned issues were overcome with the use of isotopically labeled QDs, separated by centrifugal ultrafiltration (CU) and measured by high-resolution inductively coupled plasma mass spectrometry (HR-ICP-MS), combined with the detection of free and labile metal ions by scanned stripping chronopotentiometry (SSCP). They firmly provided a thorough comprehension regarding the transformation of QDs in surface waters. The physicochemical conditions of the medium including the presence of an analog of natural organic matter and a mineral (i.e., fulvic acid and goethite), the manufactured coating of the QDs [here thioglycolic acid (TGA)], and the occurrence of added Zn in the medium were considered in the study. The overall results show that, in the absence of mineral/organic matter, the TGA ligands in solution that detached from the QD surface after dissolution control the metal speciation, especially for Cd. Conversely, in a more representative aquatic ecosystem condition (i.e., with Zn in the background media together with fulvic acid and goethite), almost no Zn or Cd dissolution from the QDs is detected. SSCP measurements reveal that the Zn complexes formed with the organic/mineral material in the system are inert, whereas the speciation model calculations indicated that Cd2+ is bound to TGA ligands in solution and organic/inorganic matter—therefore suggesting that, under the studied conditions, aquatic organisms will be exposed to a very low concentration of free and labile metal ions issued from the QDs.